2014
DOI: 10.1590/0004-2730000002831
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemic diet induces hepatic steatosis and alterations in mRNA expression of NADPH oxidase in rat livers

Abstract: Objective: This study aimed to determine whether a hypercholesterolemic diet induces hepatic steatosis, alterations in mRNA expression of NADPH oxidase subunits, and antioxidant defenses. Materials and methods: Fischer rats were divided into two groups of eight animals according to the treatment, control (C) and hypercholesterolemic diet (H). Those in group C were fed a standard diet (AIN-93M), and those of the group H were fed a hypercholesterolemic diet (25% soybean oil and 1% cholesterol). Results: The hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 39 publications
(40 reference statements)
6
12
0
1
Order By: Relevance
“…An increase in both ALT and AST was observed in the positive control group (39.83 ± 2.18 U/L and 56.00 ± 7.50 U/L, respectively) compared to the negative control (30.33 ± 2.39 U/L and 32.17 ± 3.17 U/L for ALT and AST, respectively). Abreu et al (2014) reported similar results of increased ALT and AST in hypercholesterolemic rats. This increase in the present study was significant only in the case of AST reaching about twice the value for the negative control group.…”
Section: Resultssupporting
confidence: 62%
“…An increase in both ALT and AST was observed in the positive control group (39.83 ± 2.18 U/L and 56.00 ± 7.50 U/L, respectively) compared to the negative control (30.33 ± 2.39 U/L and 32.17 ± 3.17 U/L for ALT and AST, respectively). Abreu et al (2014) reported similar results of increased ALT and AST in hypercholesterolemic rats. This increase in the present study was significant only in the case of AST reaching about twice the value for the negative control group.…”
Section: Resultssupporting
confidence: 62%
“…Dietary cholesterol is known to expand sterol pools in liver and decrease LDL receptors (LDLR) which are involved in scavenging LDL cholesterol from blood. Long chain fatty acids further suppress the hepatic LDLR expression while unsaturated fatty acids reverse the effect39, Recently, Abreu et al 40. reported that feeding Fischer rats with hypercholesterolemic diet comprising of 25% soyabean oil +1% cholesterol for 8 weeks enhanced serum cholesterol but has no effect on blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…The first group served as the control (C) and received a standard AIN-93M diet [47]. The second group (HF) received a high-fat diet (containing 25% soy oil and 1% cholesterol) [19, 48]. After two weeks, the C group rats were subdivided into C and CA experimental groups with eight animals each, balanced for weight; and the HF group were subdivided into HF and HFA experimental groups with eight animals each, balanced for weight.…”
Section: Methodsmentioning
confidence: 99%